Huoshanmycins A‒C, New Polyketide Dimers Produced by Endophytic Streptomyces sp. HS-3-L-1 From Dendrobium huoshanense - Zhu, Youjuan; Kong, Yichao; Hong, Yu; Zhang, Ling; Li, Simin; Hou, Shurong; Chen, Xiabin; Xie, Tian; Hu, Yang; Wang, Xiachang (Frontiers in Chemistry, 2022)
Three new polyketide dimers, huoshanmycins A‒C (1‒3), were reported from the fermentation broth of Streptomyces sp. HS-3-L-1, an endophyte isolated from the leaf of Dendrobium huoshanense. The dimeric structures of huoshanmycins were composed of SEK43, SEK15 or UWM4, with a unique methylene linkage. Their structures were elucidated through comprehensive 1D-/2D-NMR and HRESIMS spectroscopic data analysis. Huoshanmycins A and B (1, 2) displayed moderate cytotoxicity against MV4-11 human leukemia cell.